THE USE OF PHOTO ESSAY TO TEACH SPEAKING RECOUNT TEXT TO THE TENTH GRADERS OF SMK NEGERI 6 SURABAYA (RETAIN, 2016)
THE USE OF PHOTO ESSAY TO TEACH SPEAKING RECOUNT TEXT TO THE TENTH GRADERS OF SMK NEGERI 6 SURABAYA Drian Bintang Suryanto English Education, Faculty of Languages and Arts, State University of Surabaya (Emailku UNESA) Drs. Fahri, M.A English Education, Faculty of Languages and Arts, State University of Surabaya fahri@unesa.ac.id Abstrak Kegiatan berbicara adalah kegiatan yang tidak memerlukan banyak usaha untuk menciptakan aktifitas di dalamnya. Seorang guru tersebut bisa dengan sekejap mengkontrol aktifitas di dalam kelas sehingga siswa yang ada di dalamnya bisa belajar tanpa perlu bersusah payah, dan berpikir bahwa mereka tidak sedang berada di ruang kelas. Salah satu teknik mengajar yang bisa mengganti suasana tersebut adalah dengan menerapkan “photo essay” dengan mengikuti penjelasan yang di berikan oleh Williams dan Thompsons (2009). Photo Essay adalah bentuk lain dari esai yang telah di rubah kembali yang berisi dengan urutan foto yang mewakili tipe teks tersebut. Penelitian ini dilaksanakan di SMK NEGERI 6 SURABAYA. Peniliti mengobservasi kelas sepuluh jasa boga tiga, Observasi ini dilakukan secara natural, oleh karena itu penelitian ini di sebut kualitatif. Di pertemuan pertama diadakan senatural mungkin, untuk mengukur kemampuan siswa dalam menerima materi ketika guru menerapkan tekin pengajaran seperti biasa. Sementara pertemuan kedua dan ketiga siswa di beri pengajaran dengan photo essay. Dari penelitian tersebut, membuktikan bahwa photo essay dan perubahan suasana kelas menambah motivasi siswa untuk belajar di dalam kelas. Kejadian ini menimbulkan peningkatan kemampuan siswa dalam waktu ke waktu. Teknik ini juga menyediakan kesempatan bagi siswa untuk belajar berbicara lebih banyak. Kata Kunci: Mengajarkan Berbicara, Photo Essay, Teks Recount Abstract Speaking activity is an activity that doesn’t need a lot of effort to create the activity. The teacher can control the flow of the classroom so that the students can learn a lot of things without breaking any sweat, and thought that they are not in a classroom. One of the teaching techniques that can break the classroom atmosphere was “photo essay” following the previous research that has been done by Williams & Thompsons (2009). Photo Essay is another form of essay that has been recreates which consist with sequences of picture that represent the text’s type. This research took place in SMKN 6 Surabaya. The researcher observed tenth Food and Beverage three. The observation was conducted naturally, thus the research was called descriptive qualitative. The first meeting was held as naturally as possible, due to measure the students’ comprehension when the teacher implemented the ordinary technique. While the second and the third meetings were held with the implementation of the photo essay. From the research, it proves that photo essay and breaking the classroom atmosphere was increasing the motivation of the students to learn inside the classroom. In result, the students’ ability was increasing from time to time. This technique also provides the chance to the students to have more speaking exercise even more. Keywords: Teaching Speaking, Photo Essay, Recount Text.